Using Concept Oriented Reading Instruction (CORI) to Promote Students’ Reading Comprehension - Hilma Suryani (IJER (Indonesian Journal of Educational Research), 2017)
The problem of this study is “Does Concept Oriented Reading Instruction (CORI) enhance students’ reading achievement?” The design of this study was quasi-experimental. The sample of this study was taken from the population by using purposive sampling. The experimental group consisted of 39 students while the control group consisted of 35 students. The data were collected by using two instruments; test and questionnaire. The test was given twice to each group in order to see whether or not there was significance difference of pretest and posttest either in experimental or control group and whether or not there was significance difference of experimental and control group in terms of their posttest score. To prove the hypothesis, the data from pretest and posttest of experimental and control group were analyzed by applying paired sample t-test and independent sample t-test. The calculation was run by using SPSS computer program. The result of the study shows there was significance difference of students’ reading achievement between experimental and control group. Besides, the use of CORI as reading strategies was proved as effective reading strategies to enhance students’ reading achievement. Keywords: Concept Oriented Reading Instruction; reading strategy; reading achievement